1984
DOI: 10.1159/000179893
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hypothyroid Myopathy by Measurement of Various Serum Muscle Markers – Myoglobin, Creatine Kinase, Lactate Dehydrogenase and Their Isoenzymes

Abstract: An accurate and close follow-up of serum levels of thyroid hormones and various muscle markers (myoglobin, creatine kinase and its isoenzymes CK-MB and CK-BB, lactic dehydrogenase, α-hydroxybutyric dehydrogenase, etc.) was carried out in 10 hypothyroid patients on replacement therapy. The main muscle markers, creatine kinase and myoglobin, were elevated respectively in 9 and 6 subjects. In 1 male significant CK-MB traces were measured, while in 1 woman significant CK-BB amounts were assayed. Significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
3

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 12 publications
1
18
0
3
Order By: Relevance
“…6 Giampietro et al 90%. 7 and Soufir et al 97%. 8 This increase in CK levels in hypothyroidism is due to various mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…6 Giampietro et al 90%. 7 and Soufir et al 97%. 8 This increase in CK levels in hypothyroidism is due to various mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…In a study performed by Gianpietro et al to determined the most sensitive enzyme to investigated myopathy, the CPK was elevated in 60% cases, in the superior limit in 30% and normal in 10%, showing that this enzyme is the best biochemical marker for the investigation of myopathies, because it is a low cost method, sensitive and easy to perform 12 . The level of CPK does not relate to the clinical picture in the case of hypothyroidism, the patient may be symptomatic and have a normal CPK level, or the opposite 12,13 . The alteration of the level of CPK may vary from low elevations to extremely raised levels 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroxine (T4) affects energy metabolism. Deficient levels of T4 can lead to abnormalities of glycogenolysis, mitochondrial oxidative metabolism, and triglyceride turnover, all of which can impact muscle function [10]. Additionally, studies have linked a deficiency in skeletal muscle L-carnitine found in hypothyroid patients, which subsequently normalizes upon establishing a euthyroid state via hormone replacement [11].…”
Section: Discussionmentioning
confidence: 99%